Transformasi Pembelajaran Berbasis Scratch sebagai Strategi Penguatan Keterampilan Berpikir Komputasional - Rahim, Abdul; Nurhayati; Muhammad Lintang Cahyo Buono; Nurlela Pandiangan; Bhujangga Ayu Priyudahari; Rachmaniar (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the use of the Scratch application in education through a systematic literature review. The study used a systematic literature review method by searching articles from Scopus, Google Scholar, ERIC, IEEE Xplore, and SpringerLink. Articles that met the inclusion criteria were analyzed using thematic analysis techniques to identify patterns, pedagogical contributions, and research gaps. The data were analyzed descriptively and comparatively to assess the consistency of findings across studies. The results showed that Scratch was able to improve computational thinking skills, including understanding algorithmic concepts, problem solving, and logical reasoning. In addition, Scratch has been proven to encourage creativity and learning motivation through a project-based learning approach. Scratch is effective in reinforcing conceptual understanding across subjects such as mathematics, science, and digital literacy. However, challenges such as low teacher competence, limited ICT facilities, and a lack of structured training remain barriers to implementation. The implementation of Scratch still faces obstacles such as limited teacher competence, insufficient ICT infrastructure, and a lack of structured training. It is recommended that Scratch be integrated into project-based curricula, accompanied by teacher training and ICT infrastructure support.